Mobile therapeutic attention for treatment-resistant schizophrenia (m-RESIST): a prospective multicentre feasibility study protocol in patients and their caregivers. Issue 7 (16th July 2018) - Alonso-Solís, Anna; Rubinstein, Katya; Corripio, Iluminada; Jaaskelainen, Erika; Seppälä, Annika; Vella, Vincenzo Alberto; Caro-Mendivelso, Johanna; Caspi, Asaf; Isohanni, Matti; Unoka, Zsolt; Van der Graff, Shenja; Farkas, Kinga; et al.
Abstract : Introduction: Treatment-resistant schizophrenia (TRS) is a severe form of schizophrenia. In the European Union, approximately 40% of people with schizophrenia have TRS. Factors such as the persistence of positive symptoms or higher risk of comorbidities leave clinicians with a complex scenario when treating these patients. Intervention strategies based on mHealth have demonstrated their ability to support and promote self-management-based strategies. Mobile therapeutic attention for treatment-resistant schizophrenia ( m-RESIST), an innovative mHealth solution based on novel technology and offering high modular and flexible functioning, has been developed specifically for patients with TRS and their caregivers. As intervention in TRS is a challenge, it is necessary to perform a feasibility study before the cost-effectiveness testing stage. Methods and analysis: This manuscript describes the protocol for a prospective multicentre feasibility study in 45 patients with TRS and their caregivers who will be attended in the public health system of three localities: Hospital Santa Creu Sant Pau (Spain), Semmelweis University (Hungary) and Gertner Institute & Sheba Medical Center (Israel). The primary aim is to investigate the feasibility and acceptability of the m-RESIST solution, configured by three mHealth tools: an app, wearable and a web-based platform. The solution collects data about acceptability, usability and satisfaction, together with preliminary data on perceived quality of life, symptoms and economic variables. The secondary aim is to collect preliminary data on perceived quality of life, symptoms and economic variables. Ethics and dissemination: This study protocol, funded by the Horizon 2020 Programme of the European Union, has the approval of the ethics committees of the participating institutions. Participants will be fully informed of the purpose and procedures of the study, and signed inform consents will be obtained. The results will be published in peer-reviewed journals and presented in scientific conferences to ensure widespread dissemination. Trial registration number: NCT03064776 ; Pre-results.